Forage Development on ex-Coal Mining Land to Support of Livestock Business - Harmini Harmini (Indonesian Center for Animal Research and Development, 2019)
The availability of land for forage development is important to support cattle and buffalo production in Indonesia. The government is paying great attention to accelerate cattle and buffalo populations in Indonesia, one of of the Ministry of Agriculture program UPSUS SIWAB to increase cattle and buffalo population has been established. To support this program, sufficient forage and concentrate are crucial. Usually, the development of forage is allocated on the sub-optimal land and one alternative to sub-optimal land is ex-coal mined land. There are several challenges in forage production including pH, the composition of organic matter, low soil microorganisms and heavy metals. These problems can be minimized by adding organic matter, organic fertilizer, microorganism such fungi mycorrhizae and phytoremediation.